THE USE OF IDEA-DETAILS TECHNIQUE IN TEACHING PROCEDURE TEXT WRITING - Octavianti, Riska; Y., Y. Gatot Sutapa; ., Surmiyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak: Tujuandaripenelitianiniadalahuntukmenemukankeefektifanteknik Idea-DetailsdalampengajaranmenulisteksProseduruntuksiswakelastujuh di MTs Negeri 1 Pontianak padatahunajaran 2013/2014.Penelitianinimenggunakan Pre Experimental dalambentuk one group pretest and posttest desain. Penulismenggunakanrancanganacakkelompokdanmengambilkelas VII A untukmenjadicontohpenelitian yang terdiridari 42 siswa. Data dikumpulkanmenggunakanteknikpengukurandalambentuktesmenulis. Setelah pretest dan posttest, hasil-hasilsiswadalammenulisteksprosedurdianalisisdenganrumus Effect Size (ES). Penemuanmenunjukkanefek size perlakuanadalah 1.17. Inidikategorikansebagaiefek size yang besarkarena ES>0.8. Dengandemikian, dapatdisimpulkanbahwamengajarmenulisteksProsedurdenganmenggunakanteknik Idea-Details berhasilsecaraefektifdalammeningkatkanhasilkemampuanmenulissiswa. Kata Kunci: teknik Idea-Details, teksProsedur Abstract: The aim of this research was to find out the effectiveness of Idea-Details technique in teaching Procedure text writing for seventh grade students of MTs Negeri 1 Pontianak in academic Year 2013/2014. This research used Pre Experimental in one group pre-test post-test design. The writer used random cluster sampling to determine the participant of research. A class as part of population was taken randomly, and class VII A was taken as sample of this research which comprising of 42 students. The data was collected by using measurement technique in form of writing test. After pretest, the teacher applied the treatment. Finally, the last step was distributing the posttest. The students’ results of pre-test and post-test in writing Procedure text were analyzed by Effect Size (ES) formula. The findings showed the effect size of treatment was 1.17. It was categorized as large (ES > 0.8). Thus, teaching Procedure text writing by using Idea-Details technique was large effectively in increasing students’ writing achievement. Key words: Idea-Details technique, Procedure text